Analysis of Tax Incentive Implementation for MSME Taxpayers Affected by COVID-19 in Tomohon City - Olviane Olke Sumampouw (AIBPM Publisher, 2022)
The 2019 Corona Virus Disease (Covid-19) pandemic is a disaster for the world, including Indonesia. It has an impact on economic stability and the productivity of certain sectors in Indonesia. In response to this, the government made a policy to mitigate the impact of the Covid-19 pandemic, one of which was by establishing a Minister of Finance Regulation on Tax Incentives for Taxpayers affected by the 2019 Corona Virus Disease Pandemic (PMK Number 86 of 2020). Then from the results of initial observations that the researchers conducted by taking the example of 15 MSMEs in Manado, the results were 15 MSMEs did not know about the provision of Final Income Tax incentives on the responsibility of the government, therefore the researcher gives an opinion that many MSMEs in Manado have not taken advantage of the incentives given because they do not know that there is a provision of Final Income Tax incentives borne by the Government.Â Â